(untitled) (INTERNATIONAL SEMINAR, 2025)
This study explores the use of eco-lexicons in Modern Women Bali magazine to understand how women’s communities express environmental awareness through language. The research is based on Arran Stibbe’s (2015) ecolinguistic theory, which examines how ideology is embedded in discourse and how language shapes people’s relationship with nature. Using a qualitative descriptive method, this study analyzed five issues of Modern Women Bali published between 2022 and 2025. The data consist of written texts containing eco-lexicons related to ecology and sustainability. The results show that the magazine uses a variety of eco-lexicons representing environmental elements, pollution, natural resources, and ecological change. These linguistic features reflect both awareness and critique of human impact on the environment while promoting sustainable values and lifestyles. The findings suggest that women’s media can serve as an effective platform for fostering ecological consciousness and promoting care for the environment through discourse.